Implementasi Metode Rapid Application Development dalam Pembuatan Aplikasi Bahasa Isyarat Bagi Penyandang Tunarungu Berbasis Android (Studi Kasus : SLB Negeri Benpasi Kefamenanu) - Bukifan, Priska Vianey; Rema, Yasinta O. L; Risald,; Baso, Budiman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Sign language applications are designed to facilitate deaf people in communicating. Deaf people experience hearing impairment or loss of hearing function that is congenital or appears due to certain factors, such as infection or long-term exposure to loud noises. As a result of hearing limitations, they experience difficulties in speaking or hearing, so they are taught sign language in schools which makes it easier for them to communicate. Sign language is a means of communication that uses lip movements, body movements or facial expressions in order to convey communication messages quickly. Sign language applications are built using the RAD (Rapid Application Development) method because in the process of making applications, it can be done in a short and fast time and ensures adjustment of features from users. Android is used in the process of making this application, because of its wide use and easy access. This application provides a sign language translation feature in the form of videos so that it is easy to understand for deaf people.
Keywords: Deaf; Sign Language; RAD; Android